Comparative analysis of simulated in-situ colonization and degradation by Lentinula edodes on oak wafer and corn stalk - Mou, Chunye; Gong, Yuhua; Chen, Lianfu; Martin, Francis; Kang, Heng; Bian, Yinbing (Frontiers in Microbiology, 2023)
The depolymerization of lignocellulose biomass by white-rot fungi has been an important research topic. In this study, the white-rot Lentinula edodes was used to colonize the wood and non-wood substrates, and then hyphal transcriptional response and substrate degradation were analyzed during the spatial-temporal colonization on different type substrates to better understand the depolymerization of lignocellulose.Faster hyphal growth rate and thicker hyphal mat were observed on corn stalk in comparison to oak wafer. Coincide with the higher levels of gene transcripts related to protein synthesis expressed on corn stalk. Higher lignin oxidase activity was found on oak wafer, whereas a higher cellulase activity was observed on corn stalk containing a much higher content of soluble sugars. A larger set of carbohydrate-binding module (CBM1 and CBM20)-containing enzyme genes, including lytic polysaccharide monooxygenase (AA9), cellobiohydrolase (GH6 and GH7), glucanase (GH5), xylanase (GH10 and GH11), glucoamylase (GH15), and alpha-amylase (GH13), was significantly upregulated in the distal hyphae vertically colonizing corn stalk. The hyphae tended to colonize and degrade the secondary cell wall, and the deposited oxalate crystal suggested that oxalate may play an important role during lignocellulose degradation. In addition, lignin was degraded in priority in oak wafer. Of note, three lignin monomers were degraded simultaneously in oak wafer but sequentially in corn stalk. Our results indicated that the white-rot degradation pattern of lignocellulose is determined by the chemical composition and structure of the colonized biomass.